Transition-Metal-Catalyzed Nucleophilic Dearomatization of Electron-Deficient Heteroarenes - Jia, Jie; Hu, Fangdong; Xia, Ying (Synthesis, 2021)
In recent decades, transition-metal-catalyzed nucleophilic dearomatization of electron-deficient heteroarenes, such as pyridines, quinolines, isoquinolines and nitroindoles, has become a powerful method for accessing unsaturated heterocycles. This short review summarizes nucleophilic dearomatizations of electron-deficient heteroarenes with carbon- and heteroatom-based nucleophiles via transition-metal catalysis. A significant number of functionalized heterocycles are obtained via this transformation. Importantly, many of these reactions are carried out in an enantioselective manner by means of asymmetric catalysis, providing a unique method for the construction of enantioenriched heterocycles.1 Introduction2 Transition-Metal-Catalyzed Nucleophilic Dearomatization of Heteroarenes via Alkynylation3 Transition-Metal-Catalyzed Nucleophilic Dearomatization of Heteroarenes via Arylation4 Transition-Metal-Catalyzed Nucleophilic Dearomatization of Heteroarenes with Other Nucleophiles5 Transition-Metal-Catalyzed Nucleophilic Dearomatization with Nucleophiles Formed In Situ6 Conclusion and Outlook
Keywords: transition-metal catalysis; dearomatization; nucleophilic addition; heteroarenes; C–C bond formation